Territorial land-use planning in the context of formation the financial stability of the united local communities - Tretiak, A.; Tretiak, V.; Priadka, T.; Tretiak, N. (Land Management, Cadastre and Land Monitoring, 2017)
Territorial planning now is one of the essential attributes of management activities developed countries. The modern system of planning land- use in Ukraine now is not formed and balanced and does not provide positive results in achieving its high economic efficiency and environmental safety. Territorial planning of land use wasn’t needed by system of state and municipal administration because there are problems in the territorial land management which are related with insufficient compliance current needs of sustainable development. If planning of development in the cities (towns) is developed and makes of base planning documentation (general plans) then the area of land ownership and land use outside towns isn’t covered completely creation of land documents.        In Ukraine in most scientific research view separate aspects of influence territorial use of planning the spatial organization of economic activities of local communities.        For the new community situation in use land and natural resources became difficult, first of all through:-underestimation of the complexity and specificity of land reform during land and economic reforms in Ukraine;- local community hasn’t full information about  rights to land and other natural resources, their potential use and protection of the state;- incompetence of system solving problems of land reform in the local councils, for example : remove communities from order of land in their territories, lands of state and municipal property aren’t separated, land reform and land tenure systems, especially in agriculture are incomplete;- unsatisfactory legal and information support and protection of property rights of villagers to land and other natural resources;- ignoring the problems of putting into economic turnover of land as a capital resource and integrated approach to village territories in  development  the transformation of land relations, absence of a balanced state land politics of planning of land use and land management with local communities and mechanisms of its implementation;- lack of consistent state politics for the integrated development of land legislation, conduct and financing of state and municipal land management and land cadastre, formation of investment-attractive land-use;- very poor information infrastructure of the land market and the lack of a balanced public politics formation and development of the non-agricultural land and agricultural use;- lack of information ensuring for rural population about questions of opportunities for use of land and other natural resources in their territories in market conditions;        This can be realised through the Program use and protection of land and natural resources in the community.        As a result of their realization we can get:- increase the investment attractiveness and efficiency of use potential of land and other natural resources, environmental security of land tenure;- rationalization (optimization) of land use and creation of investment-attractive and sustainable land-use;- improving the efficiency of land lease, especially in the agricultural and recreational facilities;- increase revenues from payments for land and other natural resources to local budgets. Keywords: Territorial planning development of land use, territorial planning, united local community, problems of contemporary land-use.